DETERMINANTS OF SEXUAL BEHAVIOR AMONG ADOLESCENTS IN LOMBOK ISLAND - Musparlin Halid (Universitas Muhammadiyah Ponorogo, 2022)
This study aims to assess the risk factors for sexual behavior on adolescents in lombok Island. The research used a cross-sectional design. Samples taken by purposive sampling at Junior High School (JHS) and Senior High School (SHS) in Lombok Island amounted to 415 students. Data collection using questionnaires. The variables measured are as follows: sexual behavior, gender, age, alcohol consumption pattern (liquor), cigarette consumption pattern, parental education level, parental divorce status, peer influence, and social media influence. Descriptive data analysis and Chi-square with significant level p 0,05 and Odds Ratio (OR) with Confidence Interval (CI) 95%. There has been a strongly significant relationship between sexual behavior by sex, age, cigarette consumption patterns, alcohol consumption patterns, peer influence, social media influence, parental education level, and divorce status of parents (p 0,05). The deviant behavior caused by internal and contextual environments leads to an increase in sexual behavior frequency.